Non-autonomous Ginzburg-Landau solitons using the He-Li mapping method - Pérez Maldonado, Maximino; C. Rosu, Haret; Flores Garduño, Elizabeth (CIENCIA ergo-sum; Vol. 27 Núm. 4 (2020): Número especial "Retos de la física no lineal"DO - 10.30878/ces.v27n4a3, 2020)
We find and discuss the non-autonomous soliton solutions in the case of variable nonlinearity and dispersion implied by the Ginzburg-Landau equation with variable coefficients. In this work we obtain non-autonomous Ginzburg-Landau solitons from the standard autonomous Ginzburg-Landau soliton solutions using a simplified version of the He-Li mapping. We find soliton pulses of both arbitrary and fixed amplitudes in terms of a function constrained by a single condition involving the nonlinearity and the dispersion of the medium. This is important because it can be used as a tool for the parametric manipulation of these non-autonomous solitons.